Intrastriatal 6-OHDA lesion differentially affects dopaminergic neurons in the ventral tegmental area of prenatally stressed rats - Baier, Carlos Javier (2014)
Exposure to a variety of stressful events during the last week of pregnancy in rats interferes with the correct progeny development, which in turn leads to delays in motor development, impaired adaptation to stressful conditions, altered sexual behaviour, learning deficits, neuronal development and brain morphology. Many of these alterations have been attributed to changes in dopamine (DA) neurotransmission and occur primarily in the mesolimbic system. We found that prenatally stressed offspring showed higher levels of cells expressing tyrosine hydroxylase (TH) in the ventral tegmental area (VTA) and that these cells were more susceptible to a neurochemical insult with 6-hydroxy-DA (6-OHDA) in adulthood. Moreover, prenatally stressed rats presented differences in terms of the number and asymmetry of neuronal nitric oxide synthase-expressing cells in the VTA and nucleus accumbens, respectively. Similar to the results described for TH-expressing cells, the nitrergic systems were differentially regulated after 6-OHDA lesion in control and prenatally stressed rats. These results indicated that prenatal stress affects the dopaminergic and nitrergic systems in the mesolimbic pathway. In addition, we propose that the mesolimbic areas are more susceptible than the motor areas to a neurochemical insult during adult life.